Tanya jawab calon ibu Ariza Mohamed ; penerjemah, Agustin Rozalena; editor, Murni Irian Ningsih ; ilustrasi, Dinni Tresna Dewi - MOHAMED, Ariza; Rozalena, Agustin; Dewi, Dinni Tresna; Ningsih, Murni Irian (Khansa, 2006)
xv, 228 hlm ilus 23 cm